2004
DOI: 10.1111/j.1527-3466.2004.tb00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Portal Hypertension with NCX‐1000, a Liver‐Specific NO donor. A Review of Its Current Status

Abstract: Portal hypertension, a life threatening complication of liver cirrhosis, results from increased intrahepatic resistance and increased portal blood inflow through a hyperdynamic splanchnic system. The increased intrahepatic vascular tone is the result of an enhanced activity of endogenous vasoconstrictors and a deficiency of nitric oxide (NO) release by sinusoidal endothelial cells. These pathophysiological events provide the rational basis for using NO-based therapies for the treatment of portal hypertension. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Inflammatory stimuli, such as endotoxin and cytokines, can induce iNOS in a variety of inflammatory cells including macrophages, and neutrophils, as well as in vascular endothelium and smooth muscle. Generation and secretion of high NO concentrations by these cells may lead to perpetuation of local tissue damage, irrespective of the cause of the inflammatory response [219][220][221][222][223]. Endothelial cells, fibroblasts, or mast cells, or all three are also thought to contribute to NO generation in inflamed tissues although via calcium dependent activity.…”
Section: Local Gut Inflammation In Human Inflammatory Bowel Disease (mentioning
confidence: 97%
See 2 more Smart Citations
“…Inflammatory stimuli, such as endotoxin and cytokines, can induce iNOS in a variety of inflammatory cells including macrophages, and neutrophils, as well as in vascular endothelium and smooth muscle. Generation and secretion of high NO concentrations by these cells may lead to perpetuation of local tissue damage, irrespective of the cause of the inflammatory response [219][220][221][222][223]. Endothelial cells, fibroblasts, or mast cells, or all three are also thought to contribute to NO generation in inflamed tissues although via calcium dependent activity.…”
Section: Local Gut Inflammation In Human Inflammatory Bowel Disease (mentioning
confidence: 97%
“…Both Crohn's disease and ulcerative colitis are characterised by an abundance of activated macrophages and granulocytes in the inflamed tissue [219,220]. Inflammatory stimuli, such as endotoxin and cytokines, can induce iNOS in a variety of inflammatory cells including macrophages, and neutrophils, as well as in vascular endothelium and smooth muscle.…”
Section: Local Gut Inflammation In Human Inflammatory Bowel Disease (mentioning
confidence: 99%
See 1 more Smart Citation
“…66 It has been reported that chronic administration of thalidomide, through inhibition of endotoxin-related acceleration of hepatic fibrogenesis, significantly decreased portal pressure and IHR in cirrhotic animals ( Figure 3). 67 It is well-established that endotoxemia will stimulate macrophage and platelet activity associated with the release of inflammatory cytokines, tumor necrosis factor (TNF)a, and thromboxane A 2 in cirrhosis. 59,68e70 Further studies have shown that endotoxin-induced TNFa production is the key factor to induce liver injury and promote hepatic fibrogenesis.…”
Section: (4) Endocannabinoidsmentioning
confidence: 99%
“…By a NOtraffic protein is meant a protein with i) high efficiency of S-nitrosylation, ii) high stability of the S-nitroso form in the circulation and iii) high efficiency of S-transnitrosation into cells which need NO. As a candidate in this respect we focus on human serum albumin (HSA), because HSA is the most abundant plasma protein (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) g/L) and because endogenous S-nitrosothiols in human plasma is largely associated with HSA. 49) S-nitrosylated HSA (SNO-HSA) is significantly more stable than low molecular weight S-nitrosothiols.…”
Section: Introductionmentioning
confidence: 99%